Sustainable Transportation and Urban Development - Daniel Shefer (European Regional Science Association (ERSA), 2014)
The challenges facing transportation planners have grown continuously over the years owing to mounting problems of congestion, concerns with environmental degradation and global warming, enhanced awareness of safety, and the increasing complexity of travel behaviour patterns associated with modern life. Modern life has brought about more travel, more leisure time, and more engagement in out-of-home, non-work activities. Modern life, especially in more recent years, has also witnessed rapid population and economic growth in many urban areas and the decentralization of residential, commercial, and work places. It has also seen more women entering the labour market. Accompanying these changes has been the relaxation of some constraints, such as the need to commute at fixed hours, thus providing more degrees of freedom of travel. Because of the significantly increased alternative activities and travel patterns from which households can now choose, travel patterns have become more complicated. In addition, the total number of trips has increased, trip chaining is more frequent, and traffic peaks are becoming smoother. All this has resulted in making the analysis of travel behaviour more complex. Understanding travel behaviour is paramount in the design of various policies towards sustainable transportation development that will on the one hand support economic growth and well-being of the population and on the other hand will minimize adverse transport externalities. These externalities are especially pertinent in metropolitan areas because there the infrastructure networks are most intensively used and development densities are high. Increased externalities from motor vehicles called for the development of new policy and planning objectives toward sustainable transportation. In this regard, travel behaviour lies at the core of procedures for analysing and evaluating transportation-related measures aimed at improving urban mobility, environmental quality, safety, and at achieving a wide variety of social objectives. Policy analysis and planning, then, rely on travel behaviour studies and travel-demand models. Policy-making today requires more sophisticated tools, and these have been developed in terms of advanced models, most of them activity-based, that go into different levels of detail on various scales: spatial, temporal, and social. Together with the development of activity-based models, various specific models have been estimated and implemented in support of sustainable policy analysis, some of them as auxiliary to activity-based models and some of them as stand-alone models. The aim of this paper is to highlight and emphasize the important role of understanding travel behaviour and the complex relations between the various travel externalities to the development of sustainable urban development and transport policies.
Keywords: 330